Capacidades dinâmicas produtivas, comportamento estratégico e desempenho organizacional: um estudo nas microcervejarias artesanais - Drago, Henrique Faverzani (2023)
In today's ever-changing global business environment, organizations need to pay attention to developing innovative forms of development. In this context, it appears that the Brazilian beer market is undergoing a major transformation, with the emergence of artisanal microbreweries, which manufacture distinct and superior quality products. This new market is expanding. Therefore, the following research problem arises: Is there an influence of dynamic production capabilities and strategic behavior on the organizational performance of craft microbreweries in Rio Grande do Sul? To answer this, we sought to identify the profile of microbreweries and their managers; verify which type of strategic behavior is predominant; which dynamic productive capabilities stand out; verify the current scenario of organizational performance; verify the relationship between dynamic productive capacity and organizational performance, and whether this relationship is moderated by strategic behavior; develop and validate an instrument for measuring dynamic productive capacity; check which factors and characteristics have an impact; analyze what impacts were generated by the Covid 19 pandemic. One of the justifications for this study was due to the growth of this sector in recent years in Brazil, with in 2010 there were 114 registered breweries, and in 2022 this number rose to 1,729. The study of an applied nature, with a qualitative and quantitative approach, exploratory and based on empirical research analyzed 52 interviews using content analysis and the 119 questionnaires using structural equations, SPSS and Necessary Conditions Analysis (NCA). As a result, it was possible to identify that the predominant strategic behaviors are analytical and defensive, the dimensions of dynamic capabilities that stand out most are products, labor and production. In relation to organizational performance, it appears that companies in the metropolitan region have the worst financial performance, and companies in the southwest region have the best. Strategic behavior moderates the relationship between dynamic productive capabilities and organizational performance, with prospector behavior being the one that stood out most, influencing the relationship between the three types of organizational performance with different dimensions of dynamic productive capability. It was possible to validate the measurement instrument, which reinforced that dynamic productive capacity is a dynamic capacity, and not an operational capacity. Through content analysis, it was possible to identify the main products of microbreweries, their differences in relation to the competition, the biggest obstacles to growth, the best locations to produce craft beer, and the existence of cooperation between microbreweries. It was found that the Covid 19 pandemic brought numerous difficulties for companies, but also opportunities and innovations that continue to be used. Finally, the theoretical and empirical benefits for companies and society were mentioned.